Preconcentrations and determinations of copper, nickel and lead in baby food samples employing Coprinus silvaticus immobilized multi-walled carbon nanotube as solid phase sorbent - TOKSOY ÖNER, EBRU (ELSEVIER SCI LTD, 2019)
Preconcentrations of Cu(II), Ni(II) and Pb(II) ions by using Coprinus silvaticus immobilized multiwalled carbon nanotube (MWCNT) were investigated. Effects of important parameters on preconcentration procedure were examined. The best pH values of for Cu(II), Ni(II) and Pb(II) were found to be 6.0, 6.0 and 4.0, respectively. Flow rate of sample solution was 2.0 mL min(-1), while desorption was achieved at 1.0 mL min(-1) flow rate. Preconcentration factors were achieved as 60 for Cu(II), Ni(II) and 70 for Pb(II) (by dividing initial sample volume to final volume). LODs were calculated as 0.014, 0.016 and 0.093 ng mL(-1), respectively for Cu(II), Ni(II) and Pb(II). Accuracy of the method was checked by applying to certified reference samples. Inductively coupled plasma optical emission spectrometer (ICP OES) was employed for measurements of Cu(II), Ni(II) and Pb(II) in digested baby food samples.
Keywords: Coprinus silvaticus; Multiwalled carbon nanotube; Enrichment; Cu; Ni; Pb; Baby foods; ICP OES; METAL-IONS; ENVIRONMENTAL WATER; ACTIVATED CARBON; HEAVY-METALS; WASTE-WATER; EXTRACTION; REMOVAL; BIOSORPTION; CADMIUM; OXIDE